Structure-selected RBM immunogens prime polyclonal memory responses that neutralize SARS-CoV-2 variants of concern. - Gonzalo Almanza; Alex E Clark; Valentina Kouznetsova; Eduardo Olmedillas; Andrea Castro; Igor F Tsigelny; Yan Wu; George F Gao; Sandra L Leibel; William Bray; Erica Ollmann Saphire; Aaron F Carlin; et al. (PLoS Pathogens, 2022)
Successful control of the COVID-19 pandemic depends on vaccines that prevent transmission. The full-length Spike protein is highly immunogenic but the majority of antibodies do not target the virus: ACE2 interface. In an effort to affect the quality of the antibody response focusing it to the receptor-binding motif (RBM) we generated a series of conformationally-constrained immunogens by inserting solvent-exposed RBM amino acid residues into hypervariable loops of an immunoglobulin molecule. Priming C57BL/6 mice with plasmid (p)DNA encoding these constructs yielded a rapid memory response to booster immunization with recombinant Spike protein. Immune sera antibodies bound strongly to the purified receptor-binding domain (RBD) and Spike proteins. pDNA primed for a consistent response with antibodies efficient at neutralizing authentic WA1 virus and three variants of concern (VOC), B.1.351, B.1.617.2, and BA.1. We demonstrate that immunogens built on structure selection can be used to influence the quality of the antibody response by focusing it to a conserved site of vulnerability shared between wildtype virus and VOCs, resulting in neutralizing antibodies across variants.